A case of corneoscleral dellen after medial rectus recession combined with pterygium resection in right eye - Lin, Shi Bin; Li, Ze Yi; Zhan, Xing Kai; Cai, Jian Hao (Eye science, 2012)
A case of corneoscleral dellen after medial rectus recession combined with pterygium resection was reported. Case report A male patient aged 48 years had ghost for 1 year after acoustic neuroma resection. The patient was diagnosed with rectus paresis in the right eye. He successfully underwent medial rectus recession combined with pterygium resection. A corneoscleral dellen with a size of 2×2 mm was observed at 20 d postoperatively. The thinnest cornea was 147um, diagnosed as corneoscleral dellen, which was cured after undergoing corneal limbal stem cell transplantation with conjunctival flap. Corneoscleral dellen is non-infectious corneoscleral ulcer caused by complex reasons. Most cases recovered by using artificial tears, antibiotic ointment and eye wrap, and other patients required corneal limbal stem cell transplantation with conjunctival flap, even keratoplasty. It is recommended that the patients with strabismus combined with pterygium underwent conjunctival flap transplantation at early stage to prevent the incidence of surgical complications.